A High Road to Sustainability? Wildflower Harvesting, Ethical Trade and Social Upgrading in South Africa's Western Cape. (1st March 2016) - Bek, David; Binns, Tony; Blokker, Thijs; Mcewan, Cheryl; Hughes, Alex
Abstract : This paper evaluates the outcomes from an ambitious wildflower harvesting programme in South Africa's Western Cape, which has sought to achieve positive outcomes in terms of socio‐economic development and biodiversity conservation. Indigenous wildflowers, harvested according to conservation principles, are processed into 'Cape Flora' bouquets and sold into international and domestic markets. The principal supply chain provides an example of ethical trade due to the explicit environmental and social standards that are required at local sites of production. The incorporation of such standards represents an attempt to engender economic and social upgrading within the value chain. In this sense, the programme is consistent with dominant policy discourses, which suggest that exploiting potentially profitable niches within international trade flows represents a 'high road' to economic growth and transformation. The paper focuses upon the job creation and social impacts of the programme in the context of efforts to overcome South Africa's deeply entrenched socio‐economic disparities and high poverty levels. Despite impressive growth in production and exports during the global financial crisis, there have been mixed outcomes in terms of benefits to stakeholders at the upstream end of the supply chain. The paper concludes by considering the extent to which local initiatives operating under the framework of ethical trade possess the potential to facilitate effective social and economic upgrading.